A Comprehensive Review on the Phytochemical Constituents, Antioxidant and Anticancer Properties of Piper sarmentosum - Maizatul Ibrahim; Nur Farra Izzlyn Zulkiflee; Nor Hazwani Mohd Hasali (IIUM Press, International Islamic University Malaysia, 2022)
Introduction: Piper sarmentosum is a herbaceous plant that belongs to Piperaceae family which possesses antioxidant and anticancer properties due to its phytochemical compositions. It grows abundantly in Southeast Asia and widely explored in ethnomedicinal study.   Materials and method: This paper reviews previous scientific research data on P. sarmentosum on the aspects of its phytochemical constituents, antioxidant and anticancer properties. Related scientific articles were searched through academic search engines including Elsevier, Science Direct, Google Scholar, and IOP Scinotes, where the literatures were reviewed thoroughly. Results: The findings from the study have concluded that P. sarmentosum contain terpenoids, phenylpropanoids, flavonoids and alkaloids, as its main phytochemical contents of secondary metabolites. Extensive reports on its antioxidant potential were also recorded where P. sarmentosum were found to reduce free radicals. Researchers discovered anticancer activities were exhibited against several cancer cell lines including HepG2, HT-29, MCF-7, HeLa, MDA-MB-231 and HK-1. From the studied literatures, it can be concluded that the phytochemicals in P. sarmentosum contribute to its antioxidant and anticancer properties.  Conclusion: This research provides comprehensive and updated information on P. sarmentosum's phytochemical constituents, antioxidant and anticancer properties that could be used as references for further investigation on P. sarmentosum in pharmacological study.